Management of Sclerotinia rot of rapeseed-mustard through integrated pest management: MANAGEMENT OF SCLEROTINIA ROT OF RAPESEED-MUSTARD THROUGH IPM - ASHOK KUMAR; S SHARMA; A KATOCH (Journal of Oilseeds Research, 2015)
In vitro studies revealed maximum mycelial growth inhibition (98.5%) of Sclerotinia sclerotiorum by Trichoderma koningii isolate JMA-11 followed by DMA-8 (90.4%). Extract of Vitex negundo and Melia azedarach showed 100 per cent and 98.3 per cent inhibition ofmycelial growth of S. sclerotiorum at 5% concentration followed by 96.7 per cent and 91.7 per cent growth inhibition at 2.5% concentration, respectively. At 1% concentration, 57.6 per cent growth inhibition of the pathogen was shown by Melia azedarach followed by 55.6 per cent inhibition with Vitex negundo. Fifty nine genotypes of rapeseed-mustard screened under artificial field conditions showed lack of the resistance to S. sclerotiorum. However, ten genotypes viz., NRCG-104, NRC-DR-603, HC-0213, HC-0212, HC-9603, HC-9605, BCRS-17, Pusa Swarnim, Kiran, and PBC-9221 belonging to Brassica carinata were found to be moderately susceptible. In the integrated disease management, a combination of row spacing 45 cm, 2-3 lower leaf removal at 80 and 100 days after sowing and one spray of companion (0.2%) was found to be best treatment in reducing the disease incidence of Sclerotinia rot in Brassica napus.